Confronting (de)humanizing remote teaching practices. (September 2022) - Shin, Minsun
This colloquium discusses the critical need to reimagine human connections in the context of remote instruction necessitated by the COVID-19 pandemic. Educators should envisage humanizing and caring teaching practices, and address the needs of the whole person, in order to counteract education inequities and empower students in times of disruption and opportunity.